2009
DOI: 10.1089/ten.tea.2008.0562
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Proliferation and Differentiation Capacity of Aged Human Periodontal Ligament Stem Cells and Rejuvenation by Exposure to the Young Extrinsic Environment

Abstract: The application of periodontal ligament stem cells (PDLSCs) may be effective for periodontal regenerative therapy. As tissue regenerative potential may be negatively regulated by aging, whether aging and its microenvironment modify human PDLSCs remains a question. In this study, we compared the proliferation and differentiation capacity of PDLSCs obtained from young and aged donors. Then, we exposed aged PDLSCs to young periodontal ligament cell-conditioned medium (PLC-CM), and young PDLSCs were exposed to age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 34 publications
4
79
2
Order By: Relevance
“…If cell sheet technology is used for cell delivery, the functionality of the cell sheets used in the trials, which may be influenced by the cell populations employed [21] as well as by the methods used for cell sheet production [23][24][25], must be predicted. Previously published data have demonstrated that the multipotent capacity and regenerative potential of human PDLSCs are severely compromised with increasing donor age [26,27]. In the present study, we clarified the potential age-related impairment of the matrix production and functional properties of cell sheets derived from aging cells.…”
Section: Introductionmentioning
confidence: 62%
“…If cell sheet technology is used for cell delivery, the functionality of the cell sheets used in the trials, which may be influenced by the cell populations employed [21] as well as by the methods used for cell sheet production [23][24][25], must be predicted. Previously published data have demonstrated that the multipotent capacity and regenerative potential of human PDLSCs are severely compromised with increasing donor age [26,27]. In the present study, we clarified the potential age-related impairment of the matrix production and functional properties of cell sheets derived from aging cells.…”
Section: Introductionmentioning
confidence: 62%
“…It is frequently difficult to provide enough cells from one donor for the purpose of tissue engineering, because the proliferation and differentiation potentials in PDLSCs are variable between donors. 26,27 Additionally, the osteogenic differentiation of PDLSCs has been assessed previously, and the data show that PDLSCs generate scarce calcified nodules compared with the other types of stem cells derived from bone marrow and pulp tissue. 3 To overcome these problems, we attempted to extend the lifespan of PFs and to explore whether PFs genetically modified with hTERT and BMP4 enhance their differentiation capability.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of age on stem cell niches has been demonstrated in humans and animal models in a variety of tissues including the hippocampus (Knoth et al 2010), haematopoietic stem cell niche (Oakley and Van Zant 2010;Wagner et al 2008;Geiger et al 2007;Pearce et al 2007), skin (Gago et al 2009), dental pulp stem cell niche (Zheng et al 2009), muscle satellite stem cell niche ) and germline stem cell niches (Zhao et al 2008;Zahidov Fig. 6 Representative SEM montages of limbal rims from a a 24-year-old donor and b a 69-year-old donor.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the niche habitat is so critical for the preservation of the stem cell potency with age that exposure of stem cells from older individuals to a 'young' stem cell niche can rejuvenate hematopoietic stem cell function which normally declines with age (Zheng et al 2009;Oakley and Van Zant). The physical wearing of the niche areas has been shown to affect stem cell properties, too: in mice, thinning of the subventricular zone, a neurogenic stem cell niche, has been associated with decrease of cell proliferation and neuroblast numbers (Luo et al 2006).…”
Section: Discussionmentioning
confidence: 99%